A Analisis Perbandingan Kinerja Metode Ensemble Bagging dan Boosting pada Klasifikasi Bantuan Subsidi Listrik di Kabupaten/Kota Bogor - Cintari, Nanda Putri; Alifviansyah, Kevin; Tsabitah, Dhiya Ulayya; Sartono, Bagus; Firdawanti, Aulia Rizki (The Indonesian Journal of Computer Science, 2024)
The classification of electricity subsidy recipients is an crucial step to ensure that the government's social assistance program is distributed in a targeted manner, so an appropriate analysis method is needed. This research compares the Bagging and Boosting ensemble methods for the classification of households receiving electricity subsidies in Bogor Regency and City using Susenas 2023 data totaling 2002 households. The bagging method uses Random Forest and Extra Trees, while boosting includes CatBoost and LightGBM. The results showed that the Extra Trees method of bagging provided the best performance with 91% accuracy, 95% F1score, and 97% sensitivity. Factors such as ownership of electronic goods and modern facilities, such as ownership of air conditioners, laptops, and televisions are the most significant variables in influencing the classification of electricity subsidy recipients. With high accuracy and minimal bias, this model effectively supports data-driven policies for electricity subsidy distribution. This research is expected to be a strategic recommendation for the government to improve the effectiveness of the electricity subsidy program to be more efficient, well-targeted, and support the improvement of people's welfare.